The potential of a mobile group blog to support cultural learning among overseas students - Shao, Yinjuan; Crook, Charles (Sage, 2015)
We explored the use of mobile social software, in the form of a mobile group blog, to assist cultural learning. The potential of using this technology for cultural adaptation among overseas students was examined as those students adapted to the everyday life of studying abroad. Two pilot studies and a successful field study of a mobile group blog as used by UK overseas students are reported. A further study with prospective overseas students witnessing this ‘moblogging’ in China revealed the advantages of communicating through this technology as a form of peer-supported preparation for cultural adaptation. Potential advantages for learning a second language via this system, were highlighted as communication was interweaved with cultural adaptation and exercised in the blog entries. Given mobile internet, the language experience together with cultural observation impressively supported these students' growing confidence with time, space and imagination.